Effects of standardized ileal digestible lysine level in diets containing tribasic copper chloride on finishing pig growth performance, carcass characteristics, and fat quality - Coble, Kyle F.; Dritz, Steven S.; Usry, J.; Nemechek, Jeremiah E.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Woodworth, Jason C.; Hill, G. M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2015)
A total of 1,248 pigs (PIC 337 × 1050; initially 63.8 lb) were used in a 120-d experiment to study the effects of increasing standardized ileal digestible lysine (SID Lys) in diets with or without 150 ppm added Cu from tri-basic copper chloride (TBCC) on growth performance, carcass characteristics, and fat quality. Pens of pigs were allotted to 1 of 6 dietary treatments in a randomized complete block design with 26 pigs (similar number of barrows and gilts) per pen and 8 replications per treatment. Treatments were arranged in a 2 × 3 factorial with main effects of added TBCC (0 or 150 ppm of Cu) and SID Lys (85, 92.5, and 100% of the pig’s estimated requirement). Diets were corn-soybean meal–based with 30% dried distillers grains with solubles and 15% bakery meal. Overall (d 0 to 120), no TBCC × Lys interactions (P > 0.10) were observed for growth performance. Adding dietary TBCC tended (P < 0.10) to increase ADG and improve F/G. As SID Lys increased, ADG increased and F/G improved (linear; P < 0.05). Final BW increased (linear; P < 0.05) as SID Lys increased, and if pigs were fed diets containing TBCC (P < 0.05); however, only HCW increased with increasing SID Lys (linear; P < 0.05). Backfat iodine value (IV) was not affected by treatment; however, increasing the SID Lys level tended to increase jowl fat IV only in pigs fed TBCC (TBCC × Lys linear; P < 0.10). Feeding TBCC decreased (P < 0.02) liver a* values, resulting in decreased redness of the liver and increased (P < 0.01) liver Cu concentrations. Feed cost per pig, cost per pound of gain, and gain value all increased (linear; P < 0.05) as SID Lys increased when calculated on a constant days basis. As a result, IOFC was $2.19 lower (linear; P < 0.02) when pigs were fed only 85% of their estimated SID Lys requirement compared with those fed 100% of their requirement. The value of the weight gained during the experiment tended to increase (P < 0.10) for pigs fed diets containing TBCC. When calculating cost on a constant weight basis, adjusted F/G was improved (P < 0.05), and facility costs tended to be lower (P < 0.10) for pigs fed TBCC. Facility cost decreased (linear; P < 0.01) as SID Lys increased. In conclusion, feeding 150 ppm Cu from TBCC tended to increase ADG and F/G. More importantly, these results suggest that 100% of the estimated SID Lys requirement should be fed to achieve the highest net return when pigs are fed for a constant number of days and that TBCC cannot compensate for deficient SID Lys concentrations in finishing pig diets.
Swine Industry Day, 2014 is known as Swine Day, 2014
Keywords: Copper; Finishing pig; Lysine; Tribasic copper chloride